2018
DOI: 10.4103/ijem.ijem_585_17
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease and Type 2 diabetes mellitus

Abstract: Type 2 diabetes mellitus (T2DM) and nonalcoholic fatty liver disease (NAFLD) commonly exist together. It has been regarded as a manifestation of the metabolic syndrome. The presentations of NAFLD range from simple steatosis (NAFL), nonalcoholic steatohepatitis (NASH), and cirrhosis. NAFLD has a prevalence of 70% among T2DM patients. Overweight/obesity and insulin resistance (IR) have been strongly linked with NAFLD. Noninvasive assessment and staging of disease are based on clinical parameters such as age, sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
98
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(128 citation statements)
references
References 57 publications
(142 reference statements)
1
98
1
2
Order By: Relevance
“…Particularly, ZAG exhibits the attenuation of diseases associated with obesity, e.g., NAFLD [ 125 , 126 ]. NAFLD is a prevalent complication of T2DM [ 127 ]. ZAG can play a certain role in T2DM.…”
Section: Promising Agents Involved In Regulating Semicarbazide-senmentioning
confidence: 99%
“…Particularly, ZAG exhibits the attenuation of diseases associated with obesity, e.g., NAFLD [ 125 , 126 ]. NAFLD is a prevalent complication of T2DM [ 127 ]. ZAG can play a certain role in T2DM.…”
Section: Promising Agents Involved In Regulating Semicarbazide-senmentioning
confidence: 99%
“…Hypercholesterolemia is main cause of the NAFLD and ultrasound-based imaging techniques are cheaper and more widely available to diagnose NAFLD in the field of gastroenterology. [1] Parkinson disease (PD) is the second most common non-demyelinizan neurologic disase and its incidence is steadily increasing in the world. Although the etiology of PD remains unclear, detoriated cholesterol mechanism have been implicated in pathogenesis of PD.…”
Section: Introductionmentioning
confidence: 99%
“…Non-alcoholic steato-hepatitis is a common complication among the patients with type 2 diabetes mellitus with a prevalence of 70% and they usually co-exist as manifestation of the metabolic syndrome, which is marked with high level of insulin resistance among these patients [7,8]. To add to this complication of diabetes mellitus, a meta-analysis report concluded that the patients with diabetes mellitus may be associated with elevated risk of hepatocellular carcinoma incidence and mortality, furthermore, patients with diabetes have poor prognosis compared to their counterparts [9,10].…”
Section: Discussionmentioning
confidence: 99%